2008
DOI: 10.1159/000116360
|View full text |Cite
|
Sign up to set email alerts
|

Tree Pollen and Hospitalization for Asthma in Urban Canada

Abstract: Background: Allergy to tree pollen is common and aeroallergens have been associated with severe asthma exacerbations in the community setting. To determine the impact of different trees on asthma, we tested the association between daily hospitalizations for asthma and daily concentrations of different tree pollens in 10 large Canadian cities. Methods: Daily time-series analyses were employed to remove unwanted temporal trends. For each family or genus, results were adjusted for day of the week, temperature, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 34 publications
4
50
2
Order By: Relevance
“…Environmental factors, including pollutants, allergen exposure, psychological stress and weather conditions, may increase the risk of developing an acute asthma exacerbation in both children and adults [24][25][26][27][28][29][30]. The multiplicity of precipitating factors points towards a multifactorial cause, as well as potential interactions, which have been shown for some combinations of factors, such as pollutants [31,32].…”
Section: Infection Among Factors Precipitating Asthma Exacerbationsmentioning
confidence: 99%
“…Environmental factors, including pollutants, allergen exposure, psychological stress and weather conditions, may increase the risk of developing an acute asthma exacerbation in both children and adults [24][25][26][27][28][29][30]. The multiplicity of precipitating factors points towards a multifactorial cause, as well as potential interactions, which have been shown for some combinations of factors, such as pollutants [31,32].…”
Section: Infection Among Factors Precipitating Asthma Exacerbationsmentioning
confidence: 99%
“…Some ecological studies have investigated the association between the short-term effects of birch pollen exposure and hospital admission for asthma [9], emergency visits for rhinitis or conjunctivitis [10], antiallergic drug consumption [11,12], or mortality [13]. A few panel studies have examined the relationship between tree pollens and nasal symptoms [14,15] and asthma [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated specifically that the airborne pollens or fungal spores influence exacerbation of asthma, particularly in younger age groups [7,8,9]. A recent study has reported asthma exacerbations requiring hospital admissions to be associated with various tree pollen types [10]. There is also a recent and growing body of evidence indicating that the hornbeam is an important tree pollen allergen [11,12], however, its role in exacerbating asthma has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%